Staffing needs for unscheduled activity in obstetrics and gynecology. (February 2020) - Sentilhes, Loïc; Galley-Raulin, Fabienne; Boithias, Claire; Sfez, Michel; Goffinet, François; Le Roux, Sylvie; Benhamou, Dan; Garnier, Jean-Michel; Paysant, Sabine; Bounan, Stéphane; Michel, Christine; Coudray, Jean; et al.
Abstract: Introduction: To determine a minimum threshold of medical staffing needs (obstetricians-gynecologists, anesthesiologists-resuscitation specialists, nurse-anesthetists, pediatricians, and midwives) to ensure the safety and quality of care for unscheduled obstetrics-gynecology activity. Materials and methods: Face to face meetings of French healthcare professionals involved in perinatal care in different types of practices (academic hospital, community hospital or private practice) who belong to French perinatal societies: French National College of Gynecologists-Obstetricians (CNGOF), the French Society of Anesthesia and Resuscitation Specialists (SFAR), the French Society of Neonatology (SFN), the French Society of Perinatal Medicine (SFMP), the National College of French Midwives (CNSF), and the French Federation of Perinatal Care Networks (FFRSP). Results: Different minimum thresholds for each category of care provider were proposed according to the number of births/year in the facility. These minimum thresholds can be modulated upwards as a function of the level of care (Level 1, 2 or 3 for perinatal centers), existence of an emergency department, and responsibilities as a referral center for maternal-fetal and/or surgical care. For example, an obstetrics-gynecology department handling 3000–4500 births per year without serving as a referral center must have an obstetrician-gynecologist, an anesthesiologist-resuscitation specialist, a nurse-anesthetist, and a pediatrician onsite specifically to provide care for unscheduled obstetrics-gynecology needs and a second obstetrician-gynecologist available within a time compatible with security requirements 24/7; the number of midwives always present (24/7) onsite and dedicated to unscheduled care is 5.1 for 3000 births and 7.2 for 4500 births. A maternity unit's occupancy rate must not exceed 85 %. Conclusion: The minimum thresholds proposed here are intended to improve the safety and quality of care of women who require unscheduled care in obstetrics-gynecology or during the perinatal period.